Qur’an Manuscripts Prepared For Rulers: An Example Of The Literary Tradition Of Central Asia (The Journal of Interdisciplinary Human Studies, 2026)
This article examines manuscripts of the Holy Qur’an specially prepared for the rulers and courtiers of Central Asia. Using the example of unique manuscripts of the Timurid, Shaybanid, Kokand Khanate, and Mangit periods, it analyzes the role of the Holy Qur’an in the life of state rulers, the development of the art of manuscript book-making, and the traditions of palace librarianship. In particular, it considers the codicological features, the types of script, the decorative styles, and the seals with which the copies of the Qur’an presented to Amir Timur, Ibrahim Sultan, Khudayar Khan, and Amir Haydar were stamped. The article also addresses the preservation of these manuscripts in museums and libraries around the world and their comparative study. The results of the research show that a high-level school of the art of book-making developed in Central Asia and that manuscripts of the Holy Qur’an developed under state patronage.
Keywords: Holy Qur’an; manuscript; the art of the book; calligraphy; the Timurids; Ibrahim Sultan; Amir Timur; Khudayar Khan; endowment (waqf) seal; codicology; Central Asia; palace library